PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING BEHAVIOUR MASYARAKAT DI KOTA DENPASAR - Deviana D, Ni Putu Siska; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 5 No 8 (2016), 2016)
This study aims to describe the influence of lifestyle and fashion shopping imvolement against impulse buying behavior of society in Denpasar. The samples used in this study were 100 people responen. The data used in this study were collected using a questionnaire using a Likert scale of 5. Data were analyzed using multiple linear regression analysis. The results showed that the lifestyle and fashion shopping imvolement effect on impulse buying behavior of society in Denpasar. Based on the research results, it is advisable for the product provider or department store fashion, should provide a wide range of different fashion brands, and provide on specific programs such as interesting discounts to avoid unexpected expenditures.
Keywords: impulse buying behavior, shopping lifestyle, fashion involvemen